Status of implementation and perceptions of stakeholders on the fifteen (15)-kilometer limit of municipal waters - Espinosa, Roberto G. (University of the Philippines in the Visayas, 2001)
a study to determine the perceptions, status of implementation and recommendations of stakeholders on the 15 kilometer limit of municipal waters was conducted covering 77 respondents composed of municipal fishermen, commercial fishing boat operators, fisheries extension officers and policy makers in forty-one (41) coastal cities and municipalities in the six (6) provinces of Western Visayas. The different groups of respondents indicated their awareness of the law providing for the 15 kilometer limit of municipal waters and their stand on the policy. Majority f the respondnets from the group of municipal fishermen, fisheries extension officers and local government unit policy makers were in favor of the extension while the commercial fishing boat operators were all against it. Most of them believed that the extension was meant for equitable access to fishery resources on the part of the municipal fishermen and easier implementation of monitoring, control and surveillance operation. Problems on the lack of financial resources on the part of the local government units, weak law enforcement on illegal fishing, intrusion of commercial fishing boat operators in municipal waters and determination of the extent of 15 kilometer limit were among the problems encountered in the implementation of the policy. Generally the local government units are undertaking the necessary activities in the development, conservation and management in municipal waters particularly on the fisheries law enforcement, management of the open access situation, resource enhancement and conservation strategies and the devolved fisheries functions. Respndents were aware of the coastal resource situation and provided recommendations to better implement the policy.